PENGARUH PREDIKSI KEBANGKRUTAN TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR KEUANGAN DI BEI - NAIF, AMIR (Jurnal Akuntansi AKUNESA, 2014)
Abstract This Research aims is to examine and analyze the influence of bankruptcy prediction to stock return of financial services sector companies listed in Indonesian Stock Exchange. The samples at this study are companies listed in Indonesian Stock Exchange during period of 2010-2012. Data is collected by purposive sampling techniques and sample total 47 companies. Data is analyzed using simple linear regression. The results showed that bankruptcy prediction with Altman z-score has no effect on stock return of financial services sector companies. Altman z-score value of financial services sector companies unable to give information about companies financial condition so that why investor didn’t response and give influence on stock return.The result contrary to most of previous literature. Keywords:bankruptcy prediction, z-score, stock return